Difficulties in Translation from Turkish into Kazakh (Journal of Oriental Studies, 2017)
This article is considered the common aspects and specific featuresof the Kazakh and Turkish languages. Discusses about confusing wordsspecific to both languages, difficulties in translation from Turkish into Kazakhand inversely, as well as the common words in the dictionary of twolanguages. Gives some examples of the common words from the point ofview of parts of speech, and identifies differences in their writing. Provesthe fact of similarity of two languages not only at the level of words, butalso at the level of phrases, sentences. Describes today’s interaction of twolanguages.